The Effect of Audio Visual Media on the Skills of Translating Negotiation Text from Dialogue Form to Narrative Form of Phase E Students of UN P Laboratory Development High School - Aknensi Prikala Deria; Indriani Nisja; Ricci Gemarni Tatalia (PT. Anagata Sembagi Education, 2024)
This research aims to elucidate the impact of audiovisual media on the skills of Phase E students at the UNP Laboratory Development High School in converting negotiation texts from dialogue to narrative form. The study adopts a one-group pretest-posttest design, with a sample consisting of 31 students from Phase E1. Data collected include the students' scores in converting negotiation texts from dialogue to narrative form, assessed both before and after the implementation of audiovisual media. The findings indicate the following: First, prior to the use of audiovisual media, the students' average skill score was 70.16, placing it within the 66-75% range, which is classified as more than adequate (LdC). Second, following the use of audiovisual media, the average score increased to 80.38, within the 76-85% range, corresponding to a good qualification (B). Third, the use of audiovisual media was found to have a significant effect on the students' skills in converting negotiation texts, as evidenced by a tvalue that exceeds the critical ttable value (4.19 > 1.70). This research contributes valuable insights into the application of audiovisual media in educational contexts and underscores the importance of technology in enhancing the quality of Indonesian language instruction. The results provide a foundation for educators to develop more effective and interactive pedagogical strategies in the future.